2014
DOI: 10.1089/dia.2014.0078
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Electronic Portal Usage Among Patients with Diabetes

Abstract: The objectives of this review were (1) to examine characteristics associated with enrollment and utilization of portals among patients with diabetes and (2) to identify barriers and facilitators of electronic patient portal enrollment and utilization. PubMed and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) were systematically searched for papers reporting original research using quantitative or qualitative methods on characteristics, barriers, and facilitators associated with portal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 43 publications
4
73
1
5
Order By: Relevance
“…Also among parents with children with a chronic disease, low level of disease severity was one of the reasons for not using the portal [28]. However, a recent systematic review on the use of electronic portal usage among patients with diabetes showed mixed outcomes in this respect [29]. We may conclude that one uniform portal is not suitable for all patients and we should consider dividing a diabetes web portal immediately after the entrance in two parts: one for patients who are injecting insulin and another for patients who do not.…”
Section: Discussionmentioning
confidence: 99%
“…Also among parents with children with a chronic disease, low level of disease severity was one of the reasons for not using the portal [28]. However, a recent systematic review on the use of electronic portal usage among patients with diabetes showed mixed outcomes in this respect [29]. We may conclude that one uniform portal is not suitable for all patients and we should consider dividing a diabetes web portal immediately after the entrance in two parts: one for patients who are injecting insulin and another for patients who do not.…”
Section: Discussionmentioning
confidence: 99%
“…Only studies with a randomized controlled trial or comparative observational study design (e.g., cohort study, cross-sectional survey) were included. In addition, the references of review articles were reviewed 2,3,10,11…”
Section: Methodsmentioning
confidence: 99%
“…Previous reviews on the effectiveness of web portals in improving patient outcomes omit recently published studies on topics such as disease prevention, health disparities, and community web portals and health3,10 or the focus was on studies of web portals for a single disease 11. Our aim was to review the evidence on patient web portals for disease management, disease-specific portals, and disease prevention and to examine the disparities in portal use.…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates and initial screening of titles and abstracts, 42 papers were retrieved for detailed evaluation. [24,25,26] which were part of another main study [6,27,28], leading to a total of 20 unique reviews [3,6,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The overall process of review selection was …”
Section: Search Resultsmentioning
confidence: 99%
“…In general there was a high satisfaction and acceptance by users of patient portals [28,32,37,38,42]. Facilitators to adoption and use of patient portals were encouragement and assistance from providers and family members as well as self-engagement, while barriers included lack of skills, desire, or knowledge, technical difficulties, and lack of potential benefits [30]. Patient engagement and use of patient portals was strongly influenced by personal factors (ethnicity, education level, health literacy, health status) and health care delivery factors (provider endorsement and usability) [3].…”
Section: Narrative Synthesis Of the Evidence Of Benefitsmentioning
confidence: 99%